A Descriptive Study to Assess the Knowledge and Practices Regarding Biomedical Waste Management among the Health Personnel Working at Community Health Centers in a Tribal District. - Sonawane, Nilima; Raosaheb, Kamble (International Journal of Nursing Research, 2023)
Aim: The aim of this descriptive study was to assess out the knowledge and practices of the health personnel regarding biomedical waste management (BMWM) working at Community Health Centers in the tribal district of Maharashtra state. Research Methodology: A descriptive cross-sectional community-based study was conducted in PHC, rural hospital, and subdistrict hospital in the tribal district in the state of Maharashtra. A total of 100 health personnel working in the government setup selected as a sample by simple random sampling. The data were collected using semi-structured questionnaire and selfreported observational checklist. The data were analyzed by applying descriptive and inferential statistics. Results: Among the 100 health personnel, majority (74%) were female and 26% were male health personnel. As far as their designation was concerned, majority (62%) were staff nurses, 18% were technicians, 15% were pharmacists, and few (5%) health personnel were multipurpose health workers (MPHWs). Work experience, 14% health personnel were having experience <2 years, 3–5 years (24%), 5–10 years (20%), and 42% were having work experience, more than 10 years. According to their age, 38% health personnel were in the age group of 20–30 years, 31–40 years (31%), 41–50 years (26%), and 5% were in the age group of 51–60 years. As far as their training on BMWM was concerned, majority (82%) undergone on the job formal training. The study findings indicated that 86% health personnel having good knowledge regarding BMWM and 14% reported average knowledge. As far as their BMWM practices are concerned, majority (94%) having good practice and 5% were having average practice. There was a significant association of knowledge with qualification and their designation as P ≤ 0.05 at 0.05 level of statistical significance. Conclusion: From this study, it can be said that health personnel are aware of the BMWM and this is associated with the training programs attended and designation of them.c